1961
DOI: 10.1161/01.res.9.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-arterial Insulin on Tissue Cholesterol and Fatty Acids in Alloxan-Diabetic Dogs

Abstract: Insulin and saline were injected into the right and left femoral arteries respectively of 19 alloxan-diabetes-mellitus dogs for 1 to 28 weeks. A significant increase of artery tissue cholesterol and total fatty acids was found on comparing the insulin-administered right leg with the saline-administered left leg. Similarly, a significant increase of total fatty acids in muscle was found on comparing the right with the left leg of the alloxan-diabetes mellitus dogs. No significant differences were observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0
1

Year Published

1965
1965
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…However, none of these studies has proved that glucosamine induces insulin resistance in the absolute absence of insulin, which is always present in the blood of animals (endogenous or exogenous from insulin infusion during insulin clamp studies) or in the sera of the culture media. Besides, our observation is consistent with other earlier studies showing that hyperglycemia and hyperlipidemia do not cause as much trouble as atherosclerosis, which usually follows insulin resistance/hyperinsulinemia, in the absence of insulin (1)(2)(3)(4)(5).…”
Section: Journal Of Biological Chemistry 27097supporting
confidence: 92%
See 1 more Smart Citation
“…However, none of these studies has proved that glucosamine induces insulin resistance in the absolute absence of insulin, which is always present in the blood of animals (endogenous or exogenous from insulin infusion during insulin clamp studies) or in the sera of the culture media. Besides, our observation is consistent with other earlier studies showing that hyperglycemia and hyperlipidemia do not cause as much trouble as atherosclerosis, which usually follows insulin resistance/hyperinsulinemia, in the absence of insulin (1)(2)(3)(4)(5).…”
Section: Journal Of Biological Chemistry 27097supporting
confidence: 92%
“…However, as early as the 1940s, long before the concept of insulin resistance came to light, it was noticed that the application of insulin in T1DM was associated with the development of cardiovascular disorders (1)(2)(3)(4)(5). Since the 1960s, it has been established that the application of insulin in T1DM always leads to insulin resistance (6 -10).…”
mentioning
confidence: 99%
“…7 It has been previously demonstrated that hyperinsulinemia induces an increase in the media-tolumen ratio of small intramyocardial arterioles of spontaneously hypertensive rats 8 (defined as "hypertrophy," although no evaluation of the media cross-sectional area was performed). Cruz et al 9 reported that long-term insulin infusion into one femoral artery in the dog caused vascular hypertrophy only in the ipsilateral side. 9 Therefore, it is possible that metabolic abnormalities characteristic of NIDDM may have an important role in the genesis of structural alterations of small resistance arteries and, consequently, in the development of the organ damage and disease frequently observed in NIDDM (ie, ischemic heart disease, renal disease, and ocular damage).…”
mentioning
confidence: 99%
“…Cruz et al 9 reported that long-term insulin infusion into one femoral artery in the dog caused vascular hypertrophy only in the ipsilateral side. 9 Therefore, it is possible that metabolic abnormalities characteristic of NIDDM may have an important role in the genesis of structural alterations of small resistance arteries and, consequently, in the development of the organ damage and disease frequently observed in NIDDM (ie, ischemic heart disease, renal disease, and ocular damage).…”
mentioning
confidence: 99%
“…However, the manner in which insulin elevates blood pressure is unclear. Sympathetic activation, 1,2 sodium retention, 3 and vascular hypertrophy have been suggested 4 but never proven in a chronic model of hyperinsulinemia. Indeed, because of the vasodilatory effects of insulin, 2 it has been suggested the vasodilation may mask a prohypertensive effect.…”
mentioning
confidence: 99%